"J waves" induced after short coupling intervals: a manifestations of latent depolarization abnormality?. Issue Volume 20:Issue FI 1(2018) (24th April 2017) - Aizawa, Yoshifusa; Nakayama, Masafumi; Sato, Masahito; Okabe, Masaaki; Aizawa, Yoshiyasu; Takatsuki, Seiji; Fukuda, Keiichi
Abstract: Aims: To confirm the presence of tachycardia-induced slur or notch in the terminal portion of the QRS complexes in a general patient population. Methods and results: A tachycardia-induced J wave was defined as a slur or notch in the terminal portion of the QRS complexes newly induced at short RR intervals during atrial premature contractions (APCs) or atrial electrical stimulation in the electrophysiological study (EPS). Twenty-three out of 2000 patients with general diseases were involved. All patients with aborted sudden cardiac death, ventricular fibrillation or a family history of sudden cardiac death were excluded. The mean age was 72 ± 9 years, and 11 patients were male (47.8%). When the RR interval was shortened from 821 ± 142 ms to 464 ± 52 ms in the conducted APCs ( P  < 0.0001), J waves became diagnostic (0.02 ± 0.03 mV to 0.20 ± 0.07 mV, P  < 0.0001). J waves were confined to the inferior leads in 22 (95.7%) patients and were notched in 11 (47.8%) and slurred in 12 (52.2%) patients. The induction of J waves was accompanied by visible changes of the QRS morphology. When the post-APC RR interval was prolonged to 992 ± 305 ms ( P  = 0.0154 vs. baseline), the J waves were similar to baseline levels. During the EPS, J wave induction was confirmed during atrial stimulation. There were no characteristic clinical or ECG features in the patients with tachycardia-induced J waves. Conclusions: J waves can be newly induced by short RR intervals in a general patient population, and a conduction delay is the likely mechanism causing such J waves.